Challenges and Solutions for Keeping Maternity and Gynecology Services Functioning Comprehensively in Secondary Level Health Care Facility in COVID-19 Pandemic Situation Using a Clinical Approach - Biswas, Jayanta Kumar; Lall, Pratistha; Poddar, Soumen Das; Srivastava, Vikas; Nilakantan, Ajith (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: With the nationwide lockdown in India, and with a near-exclusive focus on the novel coronavirus disease (COVID-19) there has been a great deal of neglect in the management of other illnesses leading to significant mortality and morbidity. We aimed to assess the feasibility of keeping obstetrics & gynecology services in a secondary care hospital functioning (in terms of regional experiences and comprehensive patient care measures) in the COVID-19 pandemic situation using a clinical approach. STUDY DESIGN: All policies of the World Health Organization and other international obstetrics- gynecological recommendations or guidelines were followed in keeping the services functional. Hospital data of obstetrics and gynecology services were maintained and compared with the previous year’s data of the corresponding period (January to December) through a retrospective observational study. RESULTS: Compared to figures for 2019, in-patient admissions, surgeries, and daycare procedures performed, and deliveries conducted were reduced in total but almost approached previous levels. The number of out-patient attendance and gynecologic laparoscopic surgeries were significantly reduced mostly in the initial month of lockdown (April 2020) and thereafter. Only limited COVID-19 testing was done and there was no mortality in patients or health care workers (HCW) in the obstetrics and gynecological department. CONCLUSION: COVID-19 pandemic had caused an unprecedented global healthcare crisis. The experience and data collected from our hospital in the study period validate the ‘clinical’ working protocol that enables comprehensive maternity and gynecology care at secondary level care centers even in a pandemic situation without adverse outcomes on patients or the hospital staff.